Orchestrating School Culture: The Role of Participatory Leadership in Sustaining Daily Religious Habituation - Maun Maun; Affa Turrahmah (CV. Bimbingan Belajar Assyfa, 2025)
In today's era of globalization and disruption, students are required to possess complex non-academic skills such as spiritual resilience, discipline, and moral integrity. Integrating religious values ​​through orchestrating school culture is seen as a creative and effective management strategy to enhance these competencies. This research is motivated by the scarcity of evaluations of daily routines as a values ​​management strategy, with previous research generally focusing only on the formal curriculum or administrative leadership. This study evaluates the impact of morning assembly and communal prayer on students' readiness to learn and internalization of values ​​in the development of students' affective and psychomotor domains. The primary objective of this study is to analyze the strategic role of participatory leadership in institutionalizing religious values ​​into a sustainable school culture. Using qualitative methods with a case study design at Baitul Qur'an Junior and Senior High Schools (SMP-SMA) in Subang, data were collected through observation, in-depth interviews, and document analysis. Data were then analyzed interactively through data reduction, data presentation, and source triangulation. The results of the study indicate that participatory leadership has a significant positive impact in creating preventative social control and serves as scaffolding for the internalization of the values ​​of trust and responsibility. However, it was found that formal participation without reflective engagement had no significant effect on the depth of students' spiritual awareness. In conclusion, the integration of values ​​through daily habituation driven by participatory leadership can strengthen the school's management function and serve as a contextual form of da'wah bil-hal (Islamic outreach). The implication is that Islamic educational institutions need to manage daily rituals in a planned and reflective manner for the sustainability of student character formation in the future.